A TOUCH OF LOCAL WISDOM: THE STUDENTS’ VOICE - Dhalia Soetopo, Tri Mulyati, (Jurnal Pendidikan Bahasa, 2016)
This research aims at designing local culture based digital comics for eighth year students of SMP Negeri 1 Kalipuro, Banyuwangi, East Java, Indonesia. These are designed based on the English syllabus of reading skill and are developed in order to improve the students’ reading comprehension skill, especially in comprehending narrative texts. Also, it aims at preserving local wisdoms of Banyuwangi through English language teaching. The research and development steps comprise some steps adapted from the pattern developed by Borg and Gall. The researchers administered need analysis to 35 students in class VIII.1 in order to gather information dealing with the materials and media in English language teaching and the need on local culture based digital comics. The data was taken from questionnaire, interview, and document analysis. The results of need analysis reveal that the students need to be taught narrative texts with local culture content and a suitable interesting media in the form of digital comics.Keywords: local wisdom, need analysis, comics, reading.